Mānusha o śilpī Bidyāsāgara - Āhamada, Saphiuddina (Naoroja Kitābistāna, 1982)
Study of Ishwar Chandra Vidyasagar, 1820-1891, educationist and social activist from Bengal, and his contribution to Bengali literature.